Owady (mrówki, chrząszcze, motyle) jako biowskaźniki - Marta Marcjanek; Patrycja Słodownik; Krassimira Ilieva-Makulec (Studia Ecologiae et Bioethicae)
This paper is about bioindication, which is a method of assessing environmental conditions by using the response of organisms to changes in the environment. On the basis of available literature, some examples using selected groups of insects (ants, beetles, and butterflies) as bioindicators are discussed.